Edaravone use in acute intracerebral hemorrhage: A systematic review and meta-analysis of randomized controlled trials - Qin, Mingzhen; Feng, Luda; Yang, Chinyu; Wei, Dawei; Li, Tingting; Jiang, Ping; Guan, Jinzhi; Zhang, Xinyue; Shi, Xinyi; Liang, Ning; Lai, Xinxing; Zhou, Li; et al. (Frontiers in Pharmacology, 2022)
Background: Edaravone alleviates neurological deficits among patients with intracerebral hemorrhage; however, its effects on mortality and long-term functional outcomes remain unknown. Objective: To assess clinical outcomes associated with edaravone initiated within 7 days of symptom onset in intracerebral hemorrhage. Methods: We systematically searched PubMed, Embase, Cochrane Library, CiNii, China National Knowledge Infrastructure, Chinese VIP information, Wanfang Data, and SinoMed for relevant randomized controlled trials from their inception to May 1, 2021, and conducted a comprehensive systematic review and meta-analysis (PROSPERO registration number: CRD42019147801). All-cause mortality and long-term functional outcomes were taken as the primary outcomes. Results: A total of 38 randomized controlled trials including 3454 participants with acute intracerebral hemorrhage were included. The selected articles were of poor quality. Meta-analysis revealed edaravone could not reduce all-cause mortality (relative risk (RR) = 0.51; 95% confidence interval (CI) [0.11 to 2.32]; p = 0.38). No studies reported on long-term functional outcomes in those trials. In addition, edaravone alleviated neurological deficits (mean difference (MD) = -5.44; 95% CI [-6.44 to -4.44]; p < 0.00001), improved the activities of daily living (MD = 8.44; 95% CI [7.65 to 9.23]; p < 0.00001), reduced the hematoma volume (MD = -4.71; 95% CI [-5.86 to -3.56]; p < 0.00001), and increased treatment response (RR = 1.26; 95% CI [1.22 to 1.31]; p < 0.00001). In terms of safety outcome, there was no significant difference between edaravone group and control groups (RR = 1.67; 95% CI [0.92 to 3.06]; p = 0.09). Conclusion: Till date, edaravone does not associate with mortality reduction when initiated within 7 days of ICH onset. The effect of edaravone on long-term functional outcomes remains unknown due to the lack of data. Although edaravone alleviated neurological deficits, improved activities of daily living, and reduced hematoma volume, we cautiously interpreted the results owing to the overall poor quality and high heterogeneity of the included trials. Presently, the results are insufficient to support edaravone as a routine treatment option for acute intracerebral hemorrhage.